Acute cerebellar toxicity induced by high dose of cytarabine (HiDAC): A case report. (September 2020) - Rahmani, Hamid; Radmehr, Mojan; Hadjibabaie, Molouk; Solduzian, Mohammad
Cytarabine is a pyrimidine analogue that is used for the treatment of acute myeloid leukemia at different doses. Standard doses of cytarabine are used for induction therapy, while high doses are used for post-remission (consolidation) and relapsed/refractory treatment. One of the major side effects of its high doses is acute cerebellar toxicity occurring in 10 to 25% of patients. We report a case that developed this side effect after receiving two doses of high-dose cytarabine. The patient's symptoms improved after withholding the drug. Thereafter, the patient tolerated treatment continuation with lower doses.